Imitation in Cournot oligopolies with multiple markets - Hedlund, Jonas (Economic theory, 2015)
This paper analyzes imitation dynamics in Cournot oligopolies when firms imitate both rivaling firms and firms in other markets. The resulting tension between relative and absolute performance leads to a unique prediction strictly between the Nash equilibrium and perfectly competitive outcomes, which is fully characterized by a simple formula. The outcome becomes less competitive as the number of markets increases, i.e., as firms receive more information about firms in other markets. A link with relative payoff maximization is provided. An extension of the benchmark model reveals that sophisticated firms imitating across asymmetric markets converge to a related but somewhat less competitive outcome.
Gesehen am 15.09.2020